Oscillatory Stability Assessment of Renewable Power Systems Based on Frequency-Domain Modal Analysis - GAO Lei, MA Junchao, LÜ Jing, LIU Jianing, WANG Chenxu, CAI Xu (Shanghai Jiaotong Daxue xuebao)
The increasing penetration of the renewable energy has increased the risks of sub/super synchronous oscillations in power systems. Therefore, it is critical to accurately evaluate the oscillatory stability of renewable power systems ensuring the safe and stable operation of the systems. In this paper, a method for evaluating the oscillatory stability of renewable power systems based on frequency-domain modal analysis is investigated. First, the frequency-domain impedance or admittance models of key equipment and stations are established, including the renewable power generators and stations, transmission lines, synchronous generators, transformers, etc. Next, a system-level frequency-domain network model is constructed based on the actual system topology. Then, the oscillatory stability of the renewable power system is evaluated by solving the zeros of the determinant of the loop impedance matrix or the node admittance matrix of the system. The weak points of the system are identified using the participated matrix of the weak oscillation mode, which provides reference for implementation of oscillation suppression measures. Taking the practical renewable power system in East China as an example, the oscillatory stability of the system considering the varying access capacity of renewables under different grid operating conditions is assessed using the frequency-domain modal analysis method. Finally, the time-domain simulation model of the actual renewable power system is built in PSCAD/EMTDC to verify the theoretical analysis.